2020
DOI: 10.48550/arxiv.2009.14336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tetris is NP-hard even with $O(1)$ rows or columns

Abstract: We prove that the classic falling-block video game Tetris (both survival and board clearing) remains NP-complete even when restricted to 8 columns, or to 4 rows, settling open problems posed over 15 years ago [BDH + 04]. Our reduction is from 3-Partition, similar to the previous reduction for unrestricted board sizes, but with a better packing of buckets. On the positive side, we prove that 2-column Tetris (and 1-row Tetris) is polynomial. We also prove that the generalization of Tetris to larger k-omino piece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This work was generalized to show NP-completeness for k-ominos with k ≥ 4, and surprisingly also show that it is NP-complete to clear the board even for k = 2 when rotations are not allowed [34]. These reductions were further tightened in [11,12] to when the board is small and in [89] for the variant where you can rotate and then move down, but when no rotations are allowed after the block has begun to fall. The undecidability of whether a set of sequences of Tetris moves described by a regular language contains a sequence that results in an empty board has been proven [46].…”
Section: :4mentioning
confidence: 91%
“…This work was generalized to show NP-completeness for k-ominos with k ≥ 4, and surprisingly also show that it is NP-complete to clear the board even for k = 2 when rotations are not allowed [34]. These reductions were further tightened in [11,12] to when the board is small and in [89] for the variant where you can rotate and then move down, but when no rotations are allowed after the block has begun to fall. The undecidability of whether a set of sequences of Tetris moves described by a regular language contains a sequence that results in an empty board has been proven [46].…”
Section: :4mentioning
confidence: 91%
“…This work was generalized to shown NP completes for k-ominos other than 4, and surprisingly showed that it is NP-complete to clear the board even for k = 2 when rotations not allowed [43]. These reductions were further tightened in [13,12] to when the board is small and in [141] for the variant where you can rotate and then move down, but when no rotations are allowed after the block has begun to fall. The indecidability of whether a set of sequences of Tetris moves described by a regular language contains a sequence that results in an empty board [64].…”
Section: Related Workmentioning
confidence: 97%